Aprovechamiento de hojas de variedades de cacao (Theobroma cacao L.) nacional forastero y trinitario, con dos estadíos, fisiológico foliares, para la obtención de una infusión - Fonseca Peralta, Dagmar Elena (2019)
This research was carried out at the State Technical University of Quevedo of the Faculty of Livestock Sciences. It was carried out in the Laboratories of Chemistry, Biochemistry and Bromatology, located in the Experimental Finca "La María" located at km 7 1/2 of the Quevedo – El Empalme highway, San Felipe Campus, Canton Mocache, Province of Los Ríos. With the following geographic coordinates 01-06' south latitude and 79-29' West latitude. At a height of 120 meters above sea level. The objective of this study was to evaluate the physical quality of the leaves and the microbiological and organoleptic quality of infusions made from the variety cocoa leaves (National, Forase and Trinitarian). A completely random block design was used in divided plots as the first factor or large plot the varieties of cocoa (National, Forastero and Trinitario) as a small plot cocoa leaves (young – upper part of the tree and mature – lower part of the tree) with lower part of the tree) with three repetitions. For the mean comparison, the Tukey test (p<0.05) was applied. The physical variables that were measured were: pH with an average of 6.64., brix grades 1.44%., humidity 11.02% and ash 11.67%; E. coli/Coliform which I have no ufc/gr. In relation to organoleptic analyses the T6 had better color, the T5 better smell and the T1 better taste and acceptability. It is concluded that the results obtained from the physical and microbiological analyses comply with NTE INEN 2381: Tea and NTE INEN 2392: Aromatic herbs, while organoleptic analyses according to the interval scale, T1 showed greater acceptability on the part of the tasters. Keywords: cocoa, cocoa varieties, leaves, pruning, aromatic herbs, sensory analysis